2007
DOI: 10.1093/humrep/dem150
|View full text |Cite
|
Sign up to set email alerts
|

Post-neonatal hospitalization and health care costs among IVF children: a 7-year follow-up study

Abstract: The incidence of multiple births increases the utilization of post-neonatal health care services and costs among IVF children in comparison to naturally conceived children. Increased hospitalization and costs were also seen among IVF singletons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
0
27
0
4
Order By: Relevance
“…However, some reports have suggested that ART children are more likely to have childhood illnesses Källén et al, 2005;Koivurova et al, 2007;Ludwig et al, 2009). A multi-center cohort study encompassing 540 ICSI, 437 IVF, and 538 NC children suggested a significantly higher risk of childhood illness, surgery, requiring medical care, and being admitted to hospital in ART-conceived children.…”
Section: Physical Healthmentioning
confidence: 99%
“…However, some reports have suggested that ART children are more likely to have childhood illnesses Källén et al, 2005;Koivurova et al, 2007;Ludwig et al, 2009). A multi-center cohort study encompassing 540 ICSI, 437 IVF, and 538 NC children suggested a significantly higher risk of childhood illness, surgery, requiring medical care, and being admitted to hospital in ART-conceived children.…”
Section: Physical Healthmentioning
confidence: 99%
“…Another frequently heard argument in favor singleton deliveries involves the allegedly higher costs for twin outcomes after infertility treatments (43)(44)(45)(46)(47)(48). However, once again the literature uses incorrect statistical considerations.…”
Section: The Cost Argumentmentioning
confidence: 99%
“…Other studies compared both IVF singletons with naturally conceived singletons and IVF twins with naturally conceived twins [42-45]. Although these studies provided figures about the long-term health status of IVF twins and IVF singletons, no statistics were presented and no conclusions were drawn regarding the comparison between IVF twins and IVF singletons.…”
Section: Introductionmentioning
confidence: 99%
“…respiratory diseases, pneumonia, obstructive bronchitis, asthma, juvenile arthritis and neurological signs. Another study of Koivurova et al [42] showed that risks of having diagnoses related to diseases affecting the central nervous system were higher for IVF twins. Furthermore, the proportion of children with low weight, low height and inability to perform at least one developmental test was higher in the IVF twin group compared to singletons for several age categories up to three years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation